N-acetylcysteine prevents catheter occlusion and inflammation in catheter associated-urinary tract infections by suppressing urease activity - Manoharan, Arthika; Farrell, Jessica; Aldilla, Vina R.; Whiteley, Greg; Kriel, Erik; Glasbey, Trevor; Kumar, Naresh; Moore, Kate H.; Manos, Jim; Das, Theerthankar (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Proteus mirabilis is a key pathobiont in catheter-associated urinary tract infections (CA-UTIs), which is well known to form crystalline biofilms that occlude catheters. Urease activity alkylates urine through the release of ammonia, consequentially resulting in higher levels of Mg2+ and Ca2+ and formation of crystals. In this study, we showed that N-acetyl cysteine (NAC), a thiol antioxidant, is a potent urease inhibitor that prevents crystalline biofilm formation. Methods To quantify urease activity, Berthelot’s method was done on bacterial extracts treated with NAC. We also used an in vitro catheterised glass bladder model to study the effect of NAC treatment on catheter occlusion and biofilm encrustation in P. mirabilis infections. Inductively-coupled plasma mass spectrometry (ICP-MS) was performed on catheter samples to decipher elemental profiles. Results NAC inhibits urease activity of clinical P. mirabilis isolates at concentrations as low as 1 mM, independent of bacterial killing. The study also showed that NAC is bacteriostatic on P. mirabilis, and inhibited biofilm formation and catheter occlusion in an in vitro. A significant 4-8log10 reduction in viable bacteria was observed in catheters infected in this model. Additionally, biofilms in NAC treated catheters displayed a depletion of calcium, magnesium, or phosphates (>10 fold reduction), thus confirming the absence of any urease activity in the presence of NAC. Interestingly, we also showed that not only is NAC anti-inflammatory in bladder epithelial cells (BECs), but that it mutes its inflammatory response to urease and P. mirabilis infection by reducing the production of IL-6, IL-8 and IL-1b. Discussion Using biochemical, microbiological and immunological techniques, this study displays the functionality of NAC in preventing catheter occlusion by inhibiting urease activity. The study also highlights NAC as a strong anti-inflammatory antibiofilm agent that can target both bacterial and host factors in the treatment of CA-UTIs.